Sigilo no fim da cadeia de reciclagem: A reciclagem de resíduos plásticos em Surabaya, Indonésia - Colombijn, Freek (ILUMINURAS, 2020)
Resumo: A reciclagem de plásticos é um processo distribuído ao longo de uma extensa cadeia ("chain", no jargão em inglês) de abastecimento de reciclagem. O estigma negativo associado ao plástico reciclado, na Indonésia, é dirigido das fábricas para os catadores, negociantes de lixo e trituradores que trabalham manualmente os resíduos a partir dos quais o plástico reciclado é selecionado. O afastamento da fonte não só permite que as fábricas se livrem desse estigma de trabalhar com o lixo, como também que se distanciem do que se passa anteriormente na cadeia de abastecimento. Não são responsabilizados por uma possível má gestão ambiental ou social na separação dos resíduos de plástico. As fábricas, no entanto, conseguem manter o controlo sobre esta cadeia de abastecimento, estabelecendo normas para os materiais que aceitam. As fábricas têm o poder de declarar que fornecedor está de acordo com as normas e qual o que não está. Palavras-chave: reciclagem. cadeia de valor. cadeia de abastecimento. resíduos plásticos. Indonésia. produção de plásticos reciclados SECRECY AT THE END OF THE RECYCLING CHAIN: THE RECYCLING OF PLASTIC WASTE IN SURABAYA, INDONESIA Abstract: The aim of this article is to address the question: Why companies which produce or use pellets made from recycled plastics choose a strategic invisibility for their activities. The recycling of plastics is a process spread over an extended recycling supply chain. The negative stigma associated with recycled plastic in Indonesia is directed away from the factories towards the waste-pickers, junk-dealers and grinders who work the waste manually from which the recycled plastic is selected. Their remoteness from the source not only allows the factories to shake off the opprobrium of working with waste, they can also distance themselves from what goes on earlier in the supply chain. They are not held accountable for possible environmental or social mismanagement in the sorting of plastic waste. The factories, nevertheless, manage to maintain control over this supply chain by setting standards for the materials they accept. The factories have the power to declare which supplier is up to standard and which is not and have the alternative of opting for virgin plastic made from mineral oil, which keeps prices of recycled plastic low. This conspicuous invisibility is convenient for all involved in the recycling industry in the short run, but more openness would be better for all sides. Keywords: recycling. value chain. supply chain. plastic waste. Indonesia. production of recycled plastics